2018
DOI: 10.1111/hequ.12161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mobilities on the research output and its multidisciplinarity of academics in Hong Kong and Macau: An exploratory study

Abstract: This article explores how the past mobilities of academics affect their current research output (and its multidisciplinarity). Five types of mobility are used simultaneously in the analysis. Field mobility and transnational educational mobility are associated with academics' educational path, whereas transnational job mobility, intra‐sectoral job mobility and inter‐sectoral job mobility refer to their career path. The analysis is based on a representative sample of academics based in Hong Kong and Macau. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 78 publications
(130 reference statements)
1
13
0
Order By: Relevance
“…Intersectoral mobility only assumes a negative effect on publications when the number of non-academic jobs exceeds a threshold, but a one-time move to work in the government, a firm or another organisation outside academia does not seem to have an impact compared with academics who have never worked in a non-academic job. These two results are aligned with the previous findings in the literature (e.g., Horta et al, 2018). Intrasectoral mobility does not seem to play a role in publication quality, but intersectoral mobility assumes a negative effect up to a determined number of jobs outside academia, after which there is a reverse trend associated with having held several of these jobs.…”
Section: Procedures and Variablessupporting
confidence: 91%
See 3 more Smart Citations
“…Intersectoral mobility only assumes a negative effect on publications when the number of non-academic jobs exceeds a threshold, but a one-time move to work in the government, a firm or another organisation outside academia does not seem to have an impact compared with academics who have never worked in a non-academic job. These two results are aligned with the previous findings in the literature (e.g., Horta et al, 2018). Intrasectoral mobility does not seem to play a role in publication quality, but intersectoral mobility assumes a negative effect up to a determined number of jobs outside academia, after which there is a reverse trend associated with having held several of these jobs.…”
Section: Procedures and Variablessupporting
confidence: 91%
“…Some studies have suggested that academics who are never mobile and remain working at the university that conferred their PhD tend to produce fewer publications than those who move between universities (e.g., Horta, 2013). Other studies have reported similar results but found that the relationship between job mobility and research outputs and outcomes is not linear and that as the number of jobs increases, the gains from mobility in relation to research output and outcome indicators decrease (Horta et al, 2018). However, some studies, such as that by Alipova and Lovakov (2017), have found no differences in research output and outcomes between academics that have never moved between universities and those that have.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this theory, researchers mobilize internationally to achieve promotion and development. Horta et al (2018) explored different types of mobility and confirmed that transnational job mobility exerted positive effects on research output. Compared to researchers with no international mobility experience, those with such experience show a significantly higher level of international cooperation, a significantly higher IF, an average citation rate, and a significantly lower ratio of uncited articles (Kato & Ando, 2013).…”
Section: Introductionmentioning
confidence: 96%